ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI OUTPUT PRODUKSI TERNAK BABI DI KABUPATEN MANOKWARI - Stepanus Pakage; S Y Randa; Sara Yulanda Demetouw; Alnita Baaka (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2023)
This study's objective is to determine the factors that affect the output of pig production in Manokwari Regency. This survey included 30 local pig producers in total. Direct observation and questionnaires were used to gather data. The data can be analyzed using multiple regression. The results showed that the factors influencing the output of pig production in Manokwari Regency were the breeder's age, land and litter size. With an average breeder age of 45.30 years with an average ownership of 8.21 m2 and an average litter size of 5.63 tails.